Integrative approaches in remote sensing and GIS for assessing climate change impacts across Malaysian ecosystems and societies - Ricky Anak Kemarau; Stanley Anak Suab; Oliver Valentine Eboy; Zulfaqar Sa’adi; Daniel Ugih Echoh; Zaini Sakawi (MDPI, 2025)
Climate change presents significant problems to Malaysia, impacting its ecology and socio-economic structure through modified precipitation patterns, heightened flooding, coastal erosion, and agricultural susceptibility. This review methodically evaluates the utilization of remote sensing (RS) and geographic information systems (GISs) in comprehending these effects, employing a systematic approach following the PRISMA protocol. Through the examination of peer-reviewed papers from 2010 to 2024, we underscore the progress in remote sensing (RS) and geographic information system (GIS) technologies and their contribution to improving the spatial analysis of climate change impacts. Our research indicates considerable regional variations in the effects of climate change, highlighting the need for customized adaptation and mitigation efforts. The research Illustrates how advancements In remote sensing (RS) and geographic information systems (GISs) have enhanced forecasting skills and real-time surveillance, offering essential insights into ecosystem susceptibilities and socio-economic threats. This analysis underscores the necessity for cohesive policy strategies that leverage remote sensing and geographic information system insights to tackle the complex difficulties posed by climate change in Malaysia while pushing for additional research on the amalgamation of artificial intelligence and big data analytics to bolster climate resilience.